Bases para la mejora genética en Gerbera hybrida (Repertorio Científico, 2020)
Gerbera hybrida, popularly known as Daisy of Japan, is an ornamental plant par excellence that is grown in almost all regions of the planet, both as a potted plant and to be used as a cut flower. Its inflorescences have a long post-harvest duration, being very suitable for making flower arrangements. The modern gerbera is the result of the hybridization between Gerbera jamesonii, Gerbera viridifolia and possibly other species, so it can be called tales such as: Gerbera jamesonii hybrida, Gerbera jamesonii hybrids or Gerbera hybrida. As it is a cultivated plant, various genetic improvement programs have been developed in different countries, but most of the data in classical genetics without applying the use of molecular tools. In Cuba, work has not yet been done on the improvement of this crop, which would be very important considering the problems that arise today, such as the low germination of seeds. The objective of this work is to make a description of the floral biology of this species in order to support the start of an improvement program. In addition, a study of the antecedents in genetic improvement at an international level was carried out, such as: the karyotyping of the species, studies of genetic diversity, heritability, genetic mapping, study of regulatory genes, and other aspects of reproductive biology such as playback modes and self-incompatibility systems.
Keywords: daisy of Japan; Gerbera hybrida; plant breeding; floral biology